HE- and EH-hybrid waves in a circular dielectric waveguide with an anisotropic impedance surface - Shcherbinin, V.I.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2015)
The boundary-value problem for a circular dielectric waveguide with an anisotropic impedance boundary is reduced to two independent problems. Thus the hybrid waves of different types are shown to be uncoupled in such waveguide. Analytical expression is obtained for the parameter defining relative contributions of TE- and TM-polarizations to the field of a hybrid wave. Its analysis shows that hybrid waves of the one type are nearly always TE-like waves. By this criterion, they are classified as HE-waves. In contrast, waves of another type are shown to have TM-like polarization and represent EH-waves. Dispersion equation and some of its properties are presented for hybrid waves of each type. Крайову задачу для круглого діелектричного хвилеводу з анізотропною імпедансною границею було зведено до двох незалежних задач. Тим самим було показано, що в розглядуваному хвилеводі гібридні хвилі різних типів є незв'язаними. Було отримано аналітичний вираз для параметра, що визначає відносний внесок ТЕ- та ТМ-поляризацій в полі гібридної хвилі. З його аналізу виходить, що гібридні хвилі одного типу практично завжди є переважно ТЕ-хвилями. За цією ознакою вони належать до НЕ-хвиль. На противагу цьому, хвилі іншого типу мають переважно ТМ-поляризацію та являють собою ЕН-хвилі. Дисперсійне рівняння та деякі його властивості наведені для гібридних хвиль кожного типу. The boundary-value problem for a circular dielectric waveguide with an anisotropic impedance boundary is reduced to two independent problems. Thus the hybrid waves of different types are shown to be uncoupled in such waveguide. Analytical expression is obtained for the parameter defining relative contributions of TE- and TM-polarizations to the field of a hybrid wave. Its analysis shows that hybrid waves of the one type are nearly always TE-like waves. By this criterion, they are classified as HE-waves. In contrast, waves of another type are shown to have TM-like polarization and represent EH-waves. Dispersion equation and some of its properties are presented for hybrid waves of each type.